2020
DOI: 10.1007/s00405-020-05933-9
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral medialization thyroplasty in patients with vocal fold atrophy with or without sulcus

Abstract: Purpose To evaluate voice outcome after bilateral medialization thyroplasty in patients with non-paralytic glottic insufficiency due to vocal fold atrophy with or without sulcus. Methods Retrospective cohort study on 29 patients undergoing bilateral medialization thyroplasty for vocal fold atrophy (14 procedures) or atrophy with sulcus (15 procedures) between October 2012 and November 2017. Voice data were collected and analyzed for the preoperative and the 3-and 12-month postoperative time point according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Three studies 14,19,21 included exclusively unilateral procedures, and five others only bilateral procedures. 20,26,27,33,34 Sixteen studies 9,16,17,20,[22][23][24][25]28,[32][33][34][35][38][39][40] (51.6%) included follow-ups greater than 6 months, and only in two studies 9,16 (6.5%) follow-up was longer than 1 year, for every patient. Of the 31 articles, 23 (74.2%) 9,13,17,21,24,25,[27][28][29][30][32][33][34][35][36]39,40 outlined self-reported outcomes, 24 (77.4%) 9,12,17,18,[21][22][23][24][25]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies 14,19,21 included exclusively unilateral procedures, and five others only bilateral procedures. 20,26,27,33,34 Sixteen studies 9,16,17,20,[22][23][24][25]28,[32][33][34][35][38][39][40] (51.6%) included follow-ups greater than 6 months, and only in two studies 9,16 (6.5%) follow-up was longer than 1 year, for every patient. Of the 31 articles, 23 (74.2%) 9,13,17,21,24,25,[27][28][29][30][32][33][34][35][36]39,40 outlined self-reported outcomes, 24 (77.4%) 9,12,17,18,[21][22][23][24][25]…”
Section: Resultsmentioning
confidence: 99%
“…Combined simultaneous therapies address both components. Some recent papers 33,34 seem to favor a sequential approach, with medialization techniques used as the first approach, based on the European Laryngeal Society recommendation for being the least invasive possible on the treatment of scar. 42 Outcomes that most consistently improve are selfreported outcomes, with few exceptions, 9,19,28 that include experimental techniques not reproduced in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Years to come will demonstrate the advances in medical and tissue engineering in developing tools to restore the microanatomy and molecular biology in sulcus vocalis. Important breakthroughs have already been made and new studies are showing promising results [46,[61][62][63][64][65][66][67], however, further research is required until a standard technique to address sulcus vocalis is found, ending the ancient struggle of the vocal fold to freely vibrate.…”
Section: Futurementioning
confidence: 99%
“…Medialization thyroplasty procedures have been shown to result in significant voice restoration at 6 months after treatment as demonstrated by improved ratings of grade of dysphonia, roughness, breathiness, asthenia, and strain (GRBAS) scale [9]. Furthermore, research has shown significant improvements in Voice Handicap Index (VHI)-30 and Voice-Related Quality of Life (VRQOL) after type I thyroplasty procedures [10, 11]. While the benefits of medialization thyroplasty have been described, this procedure is not without risk.…”
Section: Introductionmentioning
confidence: 99%